Link Between Transformational Leadership and Creativity - AL ALI, MOHAMED (2023)
This research investigates the impact of transformational leadership (TL) on creativity within organizational settings. Employing a quantitative design approach, the study aimed to identify the relationship between TL and creativity while exploring the best practices for maximizing creative outputs. The research questions focused on understanding how TL stimulates creative thinking and determining the optimal TL strategies for enhancing creativity. Through regression and ANOVA analyses, the study found a significant positive correlation between TL and creativity, emphasizing the substantial influence of TL behaviors on fostering innovative environments. However, limitations pertaining to the sample's limited diversity and the non-normal distribution of data suggest the need for caution in generalizing the findings. While underscoring the need for further research with diverse samples and robust statistical techniques, this study encourages organizations to prioritize TL practices to promote creativity and innovation effectively. Keywords: transformational leadership, creativity, organizational environment, innovation, leadership behaviors, best practices.